Modification and Control Technology of Contact Zone of the Straight Bevel Gear - Li Yufan; Nan Boru; Gao Bin (Jixie chuandong)
The GB/T 11365-2019 provides that the tooth contact pattern of straight bevel gear is agreed by both supply and customer，and there is no direct relationship between tooth contact pattern and gear accuracy classification. During developing a high lift straight bevel gear pair for a large passenger aircraft，the straight bevel gear pair designed according to ANSI/AGMA 2009-B01 standard，the figure of the tooth contact pattern is clearly marked in the drawing，the length，position，shape and other information，in the manufacturing process control of bevel gears also have certain requirements，a good contact state of the gearbox under any working load is finally realized，and the interchangeability of the gear pair is realized，and the concept of master gear and control gear is proposed. The advanced technology of high precision straight bevel gear machining is expounded from milling technology，gear blank，fixture，cutter，program，contact zone modification technology，heat treatment deformation control，etc.